Comportamento e sexualidade em estudantes universitárias de Salvador - Andrade Sadigursky, Clésia (2002)
Introduction: The onset of sexual activity usually takes placeduring adolescence, but aspects of family planning and diseases prevention are seldom considered. Objective: Study factors relatedto university students' sexuality in Salvador. Methodology: A cross-sectional study was carried on by means of the review of clinicai files of 323 students of the Federal University of Bahia, aged between 17 and 20 years, that had used the University Medical Service Rubens Brasil from January, 1995 to December, 1999. Data regarding age of onset of sexual activity, use of contracep tive methods, and occurrence of pregnancy, abortion or delivery were studied. Results: The onset of sexual activity happened, for most of the students studied, right after adrnission to the university. Inadequate useof protection methods to avoid STDs and pregnancy was observed. Condom was the selected method for 48% of the clients, but probably not used adequat ely, nor in every sexual intercourse. There was a prevalence of 15% of pregnancy, 33,3% of which terminated. Discussion: There is a necessity to develop actions related to education about sexuality to university students, stimulating the comprehension of sex ual activity towards pleasure and postponi ng pregnancy to when it is possible to plan it.